Substitute for the Breast Milk (Sale, Distribution and Control) Act 2049 - Editor, The (Journal of Nepal Paediatric Society, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]-->DOI = 10.3126/jnps.v28i1.1407 J. Nepal Paediatr. Soc. Vol.28(1) p.34-39